HARMONIZATION OF ISLAMIC PRINCIPLES IN LAW IN INDONESIA COMPARATIVE TEXT OF THE QUR’AN AND ARTICLE 29 OF THE 1945 CONSTITUTION - Kadir, Abd; Rasiwan, Iwan; Mantu, Rahman (el-Umdah, 2025)
Indonesia is a constitutional country, its formation is based on legal principles and norms through a mutual agreement called the 1945 Constitution. The Constitution is one of the pillars of nationality in formulating the values and norms of the state. On the one hand, even though Indonesia is not a religion-based country, the 1945 Constitution substantially has very strong religious values and doctrines, especially Islam. Therefore, the author in this article will focus on analyzing how to harmonize religious values in the constitution through a comparative study of the text between the Qur'an and the content of the 1945 Constitution, specifically article 29 paragraphs 1 and 2. This research-based article uses normative juridical analysis with the type of literature research. The author traces sources in various literature, academic manuscripts, official documents, books of tafsir, then studied and then analyzed using the theory of legal harmonization. Conclusion of this article, the author finds that in principle there is a correspondence between the values of norms in article 29 paragraphs 1 and 2 of the 1945 Constitution with several verses of the Quran, for example in Al-Ikhlas, Al-Maidah, and Al-Baqarah. This connectedness can be seen in the spirit of prioritizing the values of justice and humanity. Keywords: Harmonization, UUD 1945, Islam, Qur`an, Justice.